Plan de negocios de un parador turístico de la parroquia San Juan del cantón Puebloviejo - Diaz Carrera, Evelyn Maribel (2019)
The tourist hostels are reflected as recreational, lodging, food establishments, it is one of the references in this project since it has services that make the tourist enjoy the natural and cultural of the San Juan parish and promote tourism development, Cultural and economic. This research project examines the implementation of a tourist hostel in the San Juan del Cantón Puebloviejo parish, why there is no establishment to recreate with family and friends, which this activity will promote tourism, and increase workplaces for the residents of the Canton. The services that will be offered are recreation, restoration, relaxation and entertainment; with modern facilities, trained staff and cheap prices to the general public